2018
DOI: 10.1063/1.5067399
|View full text |Cite
|
Sign up to set email alerts
|

Water droplet dynamics on a heated nanowire surface

Abstract: When a liquid droplet is deposited onto a heated surface, evaporation occurs. If the temperature of the surface is sufficiently high, bubbles are released from activated nucleation sites, making the heat transfer more efficient. However, if the temperature of the surface is further increased above the Leidenfrost point, a vapour cushion will form underneath the droplet, deteriorating the heat transfer between the surface and the droplet. In this work, we show that patterned Si nanowires can allow shifting the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Above ∼10 μm spacing, the T LFP increased as post spacing became sparser, we found that with increasing the spacings above ∼10 μm, our experimental results agree with those similar to previously established results, increasing the trend of T LFP for gentle deposition on microstructures. , However, intriguingly we found that by decreasing post spacings below ∼10 μm, T LFP increased again with the minima for the T LFP occurring at a spacing of approximately 10 μm. We also see that the maximum T LFP below 10 μm spacing is observed for the nanograss sample in line with previous reports showing similar behavior for nanotubes , and nanopillars. , These results thus suggest a crucial connection between T LFP on microstructures expanding upon limited previous work that reported high Leidenfrost temperatures for rough surfaces and porous materials …”
Section: Resultssupporting
confidence: 92%
“…Above ∼10 μm spacing, the T LFP increased as post spacing became sparser, we found that with increasing the spacings above ∼10 μm, our experimental results agree with those similar to previously established results, increasing the trend of T LFP for gentle deposition on microstructures. , However, intriguingly we found that by decreasing post spacings below ∼10 μm, T LFP increased again with the minima for the T LFP occurring at a spacing of approximately 10 μm. We also see that the maximum T LFP below 10 μm spacing is observed for the nanograss sample in line with previous reports showing similar behavior for nanotubes , and nanopillars. , These results thus suggest a crucial connection between T LFP on microstructures expanding upon limited previous work that reported high Leidenfrost temperatures for rough surfaces and porous materials …”
Section: Resultssupporting
confidence: 92%
“…It is known, that the droplet has its longest evaporation time at Leidenfrost point (T L ). [47] When the substrate temperature is higher than T L , the droplet enters into the Leidenfrost regime (Figure 4l). As shown in Figure S17, the droplet undergoing the Leidenfrost effect at 140 °C bounces without wetting the substrate because of the levitation force generated by the rapid formation of a vapor layer between the droplet and the overheated substrate (Figure 4m-III).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the LFP shift of water droplet observed on titanium oxide nanotubes was attributed to the induced capillary pressure . Moreover, recently, we concluded that a super nanowicking surface will allow maximizing the cooling in the transition boiling region because of the lift-off process and suppressing the Leidenfrost phenomenon even at higher temperatures …”
Section: Introductionmentioning
confidence: 92%